2019
DOI: 10.1037/fam0000558
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between parenting and temperament in associations with children’s executive function.

Abstract: Guided by a domain-specific approach to parenting framework, this research examined differential associations among three domains of parenting (e.g., guided learning, reciprocity, control) and children's executive function. The second aim was examine whether child surgency and negative emotionality temperament traits moderated associations among the parenting domains and children's executive function in a manner consistent with differential susceptibility theory. The sample consisted of 160 mothers and their 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
0
24
0
3
Order By: Relevance
“…As noted, due to a lack of predefined patterns of interactions that characterize the goodness‐of‐fit model, this model was mostly used as post hoc explanations for simple slope results found “unexpectedly” (e.g., Gagnon et al, 2014; Suor et al, 2019), rather than as a theoretical base for generating priori hypotheses. To address this issue, two directions are critical for refining this model: (1) clarifying what pattern of person × environment interactions is aligned with the goodness‐of‐fit conceptualization (and different from others), and (2) clarifying specificities of environmental factors and children’s factors in a given sociocultural context when generating hypotheses.…”
Section: Methods To Test the Goodness‐of‐fit Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted, due to a lack of predefined patterns of interactions that characterize the goodness‐of‐fit model, this model was mostly used as post hoc explanations for simple slope results found “unexpectedly” (e.g., Gagnon et al, 2014; Suor et al, 2019), rather than as a theoretical base for generating priori hypotheses. To address this issue, two directions are critical for refining this model: (1) clarifying what pattern of person × environment interactions is aligned with the goodness‐of‐fit conceptualization (and different from others), and (2) clarifying specificities of environmental factors and children’s factors in a given sociocultural context when generating hypotheses.…”
Section: Methods To Test the Goodness‐of‐fit Modelmentioning
confidence: 99%
“…For example, U.S. mothers of mainly African American and European American children in Head Start rated their expectations for their children's temperament and the actual levels of temperament, and the correlation of these two ratings (a goodness-of-fit index) predicted children's social skills, with a better fit predicting better social skills (Churchill, 2003). Regarding the behaviors matching approach, interactions of socialization factors and children's characteristics are investigated as predictors of children's competence (e.g., Suor et al, 2019) and social adjustment (e.g., Leerkes et al, 2009). For instance, authoritarian parenting in a sample of relatively highly educated European American families predicted higher social competence for children with low temperamental reactivity, but this type of parenting predicted lower social competence for their counterparts with high reactivity (Gagnon et al, 2014).…”
Section: Et Hod S To T E St T H E G Oodn E S S -Of-f I T Mode Lmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from the United States has shown that compared to low-plasticity peers, children high in biobehavioral plasticity had more internalizing problems at ages 5.5–12 years if there was parental discord at age 4.5, but fewer problems when the relationship between their parents was harmonious (Brock et al, 2017 ). A recent study found that in the context of lower quality guided learning, 5-year-old children high in surgency showed lower levels of executive function skills than their low-surgency peers, but in the context of higher quality guided learning, they showed higher levels of executive function than children low in surgency (Sour et al, 2019 ). In another study, boys high in positive emotionality were especially susceptible to the effects of chronic interpersonal stress on the levels of social anxiety and depression, for better or for worse (Griffith et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, to our knowledge, only one other study has identified the broadband dimension of surgency as a marker for differential susceptibility. Suor et al (2019) found that surgency interacted with parent-guided learning practices in a “for better and for worse” manner in predicting subsequent executive functioning skills. These results highlight the need to examine whether differential susceptibility operates in a domain-general or domain-specific fashion (Belsky & Pluess, 2009).…”
Section: Discussionmentioning
confidence: 97%